Let’s Tie the Knot: Marriage of Complement and Adaptive Immunity in Pathogen Evasion, for Better or Worse - Bennett, Kaila M.; Rooijakkers, Suzan H. M.; Gorham, Ronald D. (Frontiers in Microbiology, 2017)
The complement system is typically regarded as an effector arm of innate immunity, leading to recognition and killing of microbial invaders in body fluids. Consequently, pathogens have engaged in an arms race, evolving molecules that can interfere with proper complement responses. However, complement is no longer viewed as an isolated system, and links with other immune mechanisms are continually being discovered. Complement forms an important bridge between innate and adaptive immunity. While its roles in innate immunity are well documented, its function in adaptive immunity is less characterized. Therefore, it is no surprise that the field of pathogenic complement evasion has focused on blockade of innate effector functions, while potential inhibition of adaptive immune responses (via complement) has been overlooked to a certain extent. In this review, we highlight past and recent developments on the involvement of complement in the adaptive immune response. We discuss the mechanisms by which complement aids in lymphocyte stimulation and regulation, as well as in antigen presentation. In addition, we discuss microbial complement evasion strategies, and highlight specific examples in the context of adaptive immune responses. These emerging ties between complement and adaptive immunity provide a catalyst for future discovery in not only the field of adaptive immune evasion but in elucidating new roles of complement.